Progress and challenges in the prevention and control of nonalcoholic fatty liver disease - Cai, Jingjing; Zhang, Xiao‐Jing; Li, Hongliang (Medicinal research reviews, 2019)
Nonalcoholic fatty liver disease (NAFLD) is rapidly becoming the most common liver disease worldwide. Individuals with NAFLD have a high frequency of developing progressive liver disease and metabolism‐related comorbidities, which result from of a lack of awareness and poor surveillance of the disease and a paucity of approved and effective therapies. Managing the complications of NAFLD has already begun to place a tremendous burden on health‐care systems. Although efforts to identify effective therapies are underway, the lack of validated preclinical NAFLD models that represent the biology and outcomes of human disease remains a major barrier. This review summarizes the characteristics and prevalence of the disease and the status of our understanding of its mechanisms and potential therapeutic targets.